Fundraising Management Of Zakat Mal On Lembaga Amil Zakat Infak, Dan Shadaqah Muhammadiyah (Lazismu) Pekanbaru Post Pandemic - Lubis, Nurfauzy; Aisyah, Insanul; Nurhajijah, Nurhajijah (Al-Sharf: Jurnal Ekonomi Islam, 2024)
LAZISMU Pekanbaru is a zakat collection institution which collects, manages and distributes the zakat, infaq, and shadaqah. Specifically, the LAZISMU Pekanbaru has a concentration to foster and empower the economy of the people through the programs it offers to the muzakki (zakat payers) and mustahik (zakat receivers). Therefore, the Zakat Infaq and Sedekah Collection Institute of Muhammadiyah (LAZISMU) Pekanbaru must raise a large amount of zakat funds so that the programs can be carried out properly also post covid-19 pandemic . This research is a descriptive research with a qualitative approach. The results show that Pekanbaru LAZISMU based on the planning process determines the right program, and plans the steps that must be taken in order to carry out the fundraising process. Then, based on organizing function, it provides specifications of activities and tasks carried out by each member so that the fundraising process is implemented. Based on the implementation function, the fundraising of zakat mal is carried out by the muzakki who are willing to pay their zakat in the LAZISMU Pekanbaru trought e-commerce platforms.